Direct and indirect retinal input into degenerated dorsal lateral geniculate nucleus after striate cortical removal in monkey: implications for residual vision. - Kisvárday, Z; Cowey, A; Stoerig, P; Somogyi, P (1991)
We removed the striate cortex of one cerebral hemisphere in a macaque monkey, causing almost total retrograde degeneration of the corresponding dorsal lateral geniculate nucleus (dLGN) and extensive transneuronal degeneration of ganglion cells in the corresponding hemi-retina of each eye. The rare surviving geniculate projection neurons were retrogradely labelled by horseradish peroxidase (HRP) from extra-striate cortex and retinogeniculate terminals were labelled by an intraocular injection of HRP. Retinal terminals in the degenerated dLGN made synaptic contact exclusively with the dendrites of interneurons immunopositive for gamma-aminobutyric acid (GABA) in both parvocellular and magnocellular regions of dLGN. As well as being post-synaptic to retinal terminals these vesicle-containing dendrites were pre- and postsynaptic to other similar dendrites, and presynaptic to relay cells. Surviving labelled projection neurons received retinal input indirectly, via both the GABA-immunopositive interneurons and GABA-immunonegative terminals characteristic of those from the superior colliculus. In the degenerated, as opposed to the normal dLGN, about 20% of retinal terminals were GABA-immunopositive and GABA-immunoreactivity was prominently elevated in the ganglion and amacrine cell layers of the degenerated half of the retina. The optic nerve also contained numerous GABA-immunopositive axons but very few such axons were found in a normal optic nerve processed in identical manner. The surviving pathways from the retina must underlie the visual abilities that survive striate cortical removal in monkeys and human patients and may involve the degenerated dLGN as well as the mid-brain.